Synthesis, diffraction experiments, transmission electron microscopy and magnetic properties of α-Fе2О3/SiО2 nanocomposite sample - Tadić, Marin M.; Čitaković, Nada M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The sol-gel method was successfully utilized for the synthesis of the highly concentrated α-Fe2O3/SiO2 nanocomposite containing 45 wt% of hematite. TEM micrograph showed that spherical particles of 10 nm average size were evenly dissolved in glassy silica matrix. Both DC magnetization and AC susceptibility measurements indicated superparamagnetic behaviour of the system with the blocking temperature TB ≈ 65 K. Magnetization vs. field data at 300 K was successfully fitted to a weighted Langevin’s curve for superparamagnetic system and the particle size obtained from this fit was in excellent agreement with the TEM results. Several features evinced in the magnetic data pointed to the presence of non-negligible magnetic interaction between hematite nanoparticles: the weak field dependence of the magnetization as a function of temperature, narrowing of the hysteresis loop at low applied field below TB, and high value of TB for hematite nanoparticles of 10 nm in size. On the other hand, features like continuous increase of the ZFC magnetization with decreasing temperature and the absence of a plateau or a peak in the FC branch showed that no strong magnetic interactions were present in the system.The AC susceptibility study showed that the Vogel-Fulcher model for single-domain inter-acting particles was applicable, while the empirical parameters C1 = 0,055 and C2 = 0,57 that lie between values for strongly interacting systems and non-interacting systems obtained have pointed to the presence of the interactions of intermediate strength. On the basis of the above listed results, we can conclude that the system under consideration consists of interacting single- domain hematite nanoparticles with magnetic properties that are located between weakly and strongly interacting systems.